New product development (ENT600) PlushieBear / Nur Imanina Ibrahim, Madelina Entering and Sharifah Noor Hamizah Tuanku - Ibrahim, Nur Imanina; Entering, Madelina; Tuanku, Sharifah Noor Hamizah (2020)
The product is called PlushieBear, a soft toy designed to provide warmth and linked to a smart-talking app that can hold comforting conversations with individuals struggling with depression; excluding those with manic and psychotic depression. According to WHO (2017), people suffering from depression tend to isolate themselves from others. Therefore, the product is an inanimate object that is approachable for people who is uncomfortable with social live interaction.